Protecting children against exposure to content risks online in Malaysia: lessons from Australia - Mahyuddin Daud,; Juriah Abd. Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Children are the most vulnerable group in any civil society. The rise of digital technology has made them more exposed to threats of content risks through exposure to illegal and harmful Internet content. To make matters worse, legal framework regulating the Internet in Malaysia i.e. self-regulation does not mandate service providers to implement technical measures that could help reduce children’s exposure to content risks. Continuous exposure to content risk could lead to dilution of traditional values among younger generation. In order to reduce this outcome, all Internet stakeholders in Malaysia must take Internet regulation more seriously. This paper consists of three parts. The first part argues that content risks are a real threat to children in Malaysia as seen in previous studies. The second part of this paper presents the outcome of library research and focus group discussions with Malaysian Communications and Multimedia Commission (MCMC), selected Internet service providers in Malaysia and the Communications and Multimedia Content Forum (CMCF) on the regulatory measures practiced in the Malaysian self-regulation framework. This research finds non-censorship policy that does not mandate service providers to classify nor filter prohibited content to be problematic since it greatly exposed children to content risks. Furthermore, the Content Code, which guides the industrial self-regulation had no enforcement teeth, hence weakened the regulatory framework as a whole. In comparison, Australian co-regulation scheme has been focusing on protection of children online through classification and filtering measures. Lessons learnt from the Australian jurisdiction could be of reference to Malaysia in its effort to reduce children’s exposure to content risks online – as addressed in the final part of this paper.